Carbon nanotube fibers with high specific electrical conductivity: Synergistic effect of heteroatom doping and densification. (30th October 2021) - Hong, Seungki; Nam, Jungtae; Park, Seunggyu; Lee, Dongju; Park, Min; Lee, Dong Su; Kim, Nam Dong; Kim, Dae-Yoon; Ku, Bon-Cheol; Kim, Yoong Ahm; Hwang, Jun Yeon
Abstract: Low contact resistance of carbon nanotube (CNT) fibers are fundamental component to improve the electrical transport properties of CNT fibers. To reduce the contact resistance of CNT fibers, we have demonstrated synergistic effect of macroscopic densification in combination with heteroatom doping. Boron and nitrogen atoms were introduced into the hexagonal carbon lattice of the CNTs through judicious combination of high temperature thermal doping and plasma treatment. Chlorosulfonic acid (CSA) was chosen to provide selectively quaternary nitrogen on the sidewall of the CNTs. During this process, densification of the CNT fibers also proceeded, and consequently reduced the hopping or tunneling distance for inter-CNT electron transfer. As a result, we achieved remarkable electrical conductivity of the CNT fibers as high as 5, 896 Sm 2 /kg. The mechanism study by which heterogeneous conduction model proved the decrease of the electrical barrier height of the CNT fibers. These results provide a substantial step towards the use of CNT fibers as conductive materials. Graphical abstract: Image 1